Matematyka
wioletka121buzi
2018-01-01 11:53:09
1. Znajdź liczbę przeciwna do liczby (-2/3)*(2-6*1 i 1/3) / 3 i 3/5 + 1,2 : 3/5 w postaci ułamki nieskracalnego .
Odpowiedź
monisiek112
2018-01-01 17:27:10

(-2/3)*(2-6*1 i 1/3) -------------------------- = 3 i 3/5 + 1,2 : 3/5 """(-2/3) * (2 - 6 * 4/3) = ----------------------------- = """3 i 3/5 +1 i 2/10 * 5/3 """"(-2/3) *(2 - 2*4/1) = ------------------------------ = """3 i 3/5 + 12/10 * 5/3 """"(-2/3) * (2 - 8/1) = --------------------------- = """ 3 i 3/5 + 4/2 * 1/1 """""( - 2/3) * (2 - 8) = --------------------------- = """ 3 i 3/5 + 4/2 """" (- 2/3) * (-6) = -------------------- = """ 3 i 3/5 + 2 """""(-2/1) * (-2) = -------------------  = """" 5 i 3/5 """"" 4 = ----------- = """ 5 i 3/5 = 4 : 3 i 3/5= = 4 : 28/5 = = 4 * 5/28= = 20/28 = = 5/7 Liczba przeciwna do liczby 5/7 ----> 7/5 (= 1 i 2/5)

Dodaj swoją odpowiedź